PELOSI CESAREAN TYPE - Novoa, Salomón (2015)
OBJETIVE: To determine Pelosi's simplifiedcesarean?section technique associated characteristics and morbidity. DESIGN: Prospective, descriptive, observational study. SETTING: Tuman Hospital's Gynecology and Obstetrics Department, Obstetrical Service. MATERIAL AND METHODS. Forty?five pregnant women underwent the Pelosi cesarean?section teclinique. Operating time, sutures, blood loss, maternal morbidity and post?operative hospital stay were determined. RESULTS: Maternal age was between 16 and 39 year?old, usual indications included previous cesarean?sections and multiple pregnancies, surgical time was 19 minutes to 1 hour, hemoglobin loss was 3,7 to 0,5 grams, only sutures used were one No 1 chromic catgut and one No 0 monofilament nylon, hospital stay was between 36 and 72 hours and no maternal complication was registered. CONCLUSION.? Pelosi cesarean-section technique is an excellent alternative procedure for operative delivery.